Innate Immune Response in Non Alcoholic Fatty Liver Disease: An Overview of Alterations in TLR9, Macrophages, and TNFα - Supriatna, Novianti; Siregar, Nurjati Chairani (Writing Center IMERI FMUI, 2022)
Non-Alcoholic Fatty Liver Disease (NAFLD) and Alcoholic Liver Disease (ALD) are two causes of chronic liver disease. In Indonesia, NAFLD is the most common case of hepatic disease for Indonesian people. Risk factors such as obesity, diabetes mellitus, and metabolic syndrome increase the risk of developing NAFLD. About 1.5 billion people worldwide suffer from fatty liver, with a prevalence of 25-30%. Hence, it will continue to increase sharply if risk factors or diseases are not mitigated with pharmacological treatment and diet. The innate immune response induces abnormalities in fatty liver, mediated by Kupffer cells and TLR9 (Toll-Like Receptor 9), leading to inflammation via proinflammatory cytokines, like TNFα. Hepatocyte injury releases signals in the form of mitochondrial DNA enclosed in microparticles, which travels into the plasma, and are then captured by TLR9. Activation of TLR9 on Kupffer cells is the starting point of the inflammatory process in the pathogenesis of NAFLD, and it triggers other immune responses that encourage the development of steatohepatitis until a more severe liver injury occurs. The latest study found that analysis is needed to determine the immunological mechanisms and therapeutic targets associated with inflammation in fatty liver disease as evidenced by various immunological approaches.